Retinopathy of prematurity and risk factors: a prospective cohort study - Angell Linda; Muttineni Jyotsna; Karna Padmani; Karmaus Wilfried (BMC, 2005)
Abstract Background Increased survival of extremely low birth infants due to advances in antenatal and neonatal care has resulted in a population of infants at high risk of developing retinopathy of prematurity (ROP). Therapeutic interventions include the use of antenatal and postnatal steroids however, their effects on the severity of ROP is in dispute. In addition, it has not been investigated whether severe ROP is due to therapeutic interventions or due to the severity of illness. The aim of the present study was to assess the association between the incidence of severe retinopathy of prematurity (greater than stage 2 - International classification of ROP) and mechanical ventilation, oxygen therapy, gestational age, antenatal and postnatal steroids in extremely low birth weight infants. Methods Neonates admitted to the neonatal intensive care unit in Lansing, Michigan, during 1993-2000 were followed to determine factors influencing the development of severe retinopathy of prematurity. Ophthalmologic examinations were started at 6 weeks and followed until resolution. We used logistic regression to estimate the relative risk (odds ratio) associated with risk factors of ROP. Results Of the neonates with ≤ 1500 g birth weight, admitted to the neonatal intensive care unit, 85% (616/725) survived. Severe retinopathy of prematurity was detected in 7.8% of 576 neonates who had eye examinations. Neonates of lower gestational age (≤ 25 weeks and 26-28 weeks) had an increased odds ratio of 8.49 and 3.19 for the development of severe retinopathy of prematurity, respectively, compared to those 29 weeks and older. Late postnatal steroid treatment starting after 3 weeks of life showed 2.9-fold increased odds ratio, in particular administration for two weeks and more (OR: 4.09, 95% CI: 1.52-11.03). With increasing antenatal steroids courses the risk of severe retinopathy of prematurity decreased, however, it was not significant. Lower gestational age, dependence on ventilation, and use of postnatal steroids were intertwined. Simultaneous presence of these factors seems to indicate severe disease status. Conclusion Prolonged and late postnatal steroids treatment in very low birth weight infants may pose an increased risk for the development of severe retinopathy of prematurity; however, use of postnatal steroids may also be a marker for severity of illness. Further studies need to focus on biologic markers in the pathogenesis of retinopathy of prematurity and to better understand the influence of therapies.